Achieving the state of Georgia 25% HIV incidence reduction target among men who have sex with men in Atlanta through expanded use of multimodal pre-exposure prophylaxis: A mathematical model - Jeremy Fraysse; Sarah-Jane Anderson; Justin C. Smith; Derrick D. Matthews; Supriya Sarkar; Filipa de Aragao; Rob Blissett (PLoS ONE, 2025)
The US faces substantial demographic and geographic disparities in both HIV burden and access to pre-exposure prophylaxis (PrEP), an effective strategy to prevent HIV acquisition. Long-acting cabotegravir (CAB) is a novel, injectable PrEP option which demonstrated superior reduction in risk of HIV acquisition compared to daily-oral PrEP in the HPTN083 trial. We modelled the impact of increased PrEP initiations and the introduction of long-acting CAB on HIV incidence among men who have sex with men (MSM) in Atlanta, Georgia, a population with a high burden of HIV. The Georgia Department of Public Health has set an ambitious 25% HIV incidence reduction target, which could be reached with a daily-oral PrEP coverage of 42.2%. However, the target could be achieved at lower levels of PrEP coverage (34.6%) if a mix of PrEP modalities was used, such as an equal split of long-acting CAB PrEP and daily-oral PrEP. Our results clearly demonstrate that broadening access to new PrEP options has the potential to facilitate the achievement of public health HIV incidence reduction goals at plausible levels of PrEP coverage.